Investigation of the Effect of Solanum incanum on Postprandial Blood Glucose Concentration of Normoglycemic Nigerians - Okolie, V. Uchenna; Okeke, E. Chinwe; Ehiemere, O. Ijeoma; Ezenduka, O. Pauline (Pakistan Journal of Nutrition, 2009)
The effect of a Nigerian vegetable plant, Solanum incanum on postprandial blood glucose levels of normoglycemic Nigerians was investigated. Proximate analysis indicated that this vegetable contained significant amount of fiber, which is a Non-soluble Polysaccharide (NSP). The effect of the vegetable was compared with those of other indigenous vegetables also taken by diabetic patients, Vernonia amygdalina and Gongronema latifolium. A-50 g glucose was used for standard glucose tolerance test of each subject. The values were used to compare other test results. The blood glucose concentration of the subjects was determined (post absorptively) using Accu-chek active glucometer. The vegetables (50 g each) were processed according to the methods used by the patients; squeeze-wash-drink and chew-raw. They were administered to the different groups of subjects who also served as their own controls (n 8, Solanum; n 8, Vernonia; n 8, Gongronema) on separate days in randomized order. Blood glucose levels were checked at fasting (0 min) and postprandially at 30 min intervals for 2 h. Compared with other vegetables, Solanum elicited significant reductions (p<0.05) in blood glucose levels at most postprandial time points and for Area-under-curve (AUC) values. AUC reductions; Solanum, 18%; Vernonia, 15%; Gongronema, 13%). The bioactive antioxidant substances that occur naturally in stems, roots and leaves of African plants may possess insulin - like effect. The rich NSP content of Solanum incanum is also likely to be a reducing factor.